New taxa and new records of Australian Panchaetothripinae (Thysanoptera, Thripidae) - Mound, Laurence A. (Zootaxa, 2009)
A new genus and species of panchaetothripine thripid, Stosicthrips szitas, apparently related to Parthenothrips dracaenae, is described from leaves of a cultivated Grevillea (Proteaceae) in central Queensland and also at Perth, Australia. In another genus, Bhattithrips, a new species B. borealis is described from northern Australia, and the four members of this Australian genus are distinguished in a key. A species described from Southeast Asia, Astrothrips aureolus, is established and probably native to northern Australia, where it damages the leaves of an Hymenocallis cultivar (Amaryllidaceae).